Digital adaptation and linguistic change in Arabic language usage through social media - Habib, Ikhwanul; Zaki, Muhammad; Mustofa, Syaiful (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The growing use of language is a result of the rapid development of technology and social media. In the modern context, what is meant is information and communication technology. Through communication using language aims to reach an agreement and understanding. The purpose of this study is to determine the role of Arabic through social media as a universal communication tool. The method used is descriptive qualitative with a library research approach. The study area includes the fields of business economics, information dissemination, and plotik diplomacy. Data collection techniques are relevant documents and journals. Data analysis by reading, marking, and summarizing. The results prove that Arabic plays an important role in the field of business economics, this is supported by the existence of giant economic projects in Arab countries, and its geographical location is very strategic and supports the creative economy in Indonesia. Arabic is also a medium for disseminating global information. This is evidenced by the Arabic website Al-Jazeera, as well as international Arabic seminars. Technological advances also provide benefits in the field of Arabic language learning. Furthermore, the role of Arabic in the field of culture, with the holding of Al-Arabiyah Lil Funnun activities is evidence of the role of Arabic in the field of culture. While in the field of diplomacy, it certainly includes relations between countries and in the political field as evidenced by the existence of political movements such as the Arab Spring.